Moral vision and tradition : essays in Chinese ethics - Cua, A. S. (Antonio S.), 1932-2007. (Washington, D.C. : Catholic University of America Press, 1998)
"This volume offers a comprehensive philosophical study of Confucian ethics - its basic insights and its relevance to contemporary Western moral philosophy. Writer and philosopher A.S. Cua presents fourteen essays which deal with various problems arising in the philosophical explication of the nature of Chinese ethical thought." "Offering a unique analytical approach, Cua focuses on the conceptual and dialectical aspects of Confucian ethics. Among the topics discussed are: the nature and significance of the Chinese Confucian moral vision of tao; the complementary insights of Classical Taoism, namely, of Lao Tzu and Chuang Tzu; and the logical and rhetorical aspects of Confucian ethics." "Perhaps more relevant to contemporary East-West ethical discourse, several essays introduce a systematic Confucian moral philosophy. Cua concludes with a discussion of the possibility of reasoned discourse, aiming at a resolution of intercultural ethical conflict."--Jacket
Reasonable action and Confucian argumentation -- Confucian vision and experience of the world -- Forgetting morality: reflections on a theme in Chuang tzu -- Chinese moral vision, responsive agency, and factual beliefs -- Opposites as complements: reflections on the significance of Tao -- Morality and human nature -- Harmony and the Neo-Confucian sage -- Competence, concern, and the role of the paradigmatic individuals (Chün tzu) in moral education -- Between commitment and realization: Wang Yang- ming's vision of the universe as a moral community -- The possibility of a Confucian theory of rhetoric -- A Confucian perspective on self-deception -- The Confucian tradition (Tao-t'ung) -- Basic concepts of Confucian ethics -- Principles of preconditions of adjudication.
Includes bibliographical references (pages 331-345) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Ethics -- China; Philosophy, Confucian; Philosophy, Chinese; Morale -- Chine; Philosophie confucéenne.; Philosophie chinoise; PHILOSOPHY -- Ethics & Moral Philosophy; Ethics; Philosophy, Chinese; Philosophy, Confucian; China; Konfuzianismus; Philosophie; Ethik; Aufsatzsammlung; China; Ethiek; Confucianisme; China; Morale confucéenne.; Confucianisme; Morale -- Chine